50 years of invertebrate conservation under the United States Endangered Species Act—history and threats to species - Shirey, Vaughn M.; Lewthwaite, Jayme M.M.; Gawel, Ann Marie; Guzman, Laura Melissa (Frontiers in Conservation Science, 2025)
IntroductionThe United States Endangered Species Act celebrated its 50th anniversary in 2023. As a hallmark piece of environmental legislation, the Act has successfully prevented the extinction of hundreds of species. During these last 50 years, we have observed the decline of many species of invertebrates, resulting in the listing of 356 species.MethodsHere, we summarize the state of endangered invertebrates using text mining to review all listing documents, including listing decisions, species status assessments, critical habitat designations, and status reviews. In our review, we evaluate the most prevalent threats for aquatic and terrestrial invertebrates.ResultsWe found that invertebrates have been assessed and listed consistently in the past 50 years, and the last eight years have seen an uptick in status reviews. Further, we find that pollution, natural system modifications (such as dams), and intrinsic factors (such as small population sizes or number of populations) are the major contributing threats to aquatic invertebrates. On the other hand, problematic biotic factors (such as invasive species), climate change, residential and commercial development, and pollution are the major threats to terrestrial invertebrates.DiscussionOverall, our study reviews the current threats to invertebrates and provides a baseline for the next 50 years in the face of a shifting threat and conservation arena.